Application of hydroxychloroquine for IgA nephropathy - Xiao Yong-zhen; Yang Xiao (Linchuang shenzangbing zazhi)
Globally IgA nephropathy has been the most common glomerular disease.According to the guidelines of Kidney Disease: Improving Global Outcomes（KDIGO）for treating IgA nephropathy, renin-angiotensin-aldosterone system inhibitors（RAASi）may effectively alleviate proteinuria and control blood pressure, thereby significantly delaying the progression of the disease.Glucocorticoids or immunosuppressants are routinely applied.Hydroxychloroquine（HCQ）is an immunomodulatory agent for malaria and autoimmune diseases.Recent studies have demonstrated that HCQ was efficacious for persistent proteinuria in patients with IgA nephropathy.The relevant literature reports were retrieved for comprehensively reviewing the application characteristics of HCQ for IgA nephropathy.